Evaluation of parametrics for the development of vertical solar chimney ventilation in hot and humid climate - Nugroho, Agung Murti (2006)
In terms of housing passive cooling design, tropical climatic regions present the most difficult problem to solve. A good dwelling design can keep the indoor environment favorable and comfortable during most of the year without the use of any mechanical devices. This can be accomplished by various techniques such as the use of radiant barrier, insulation materials, and natural ventilation. Depending on ambient conditions, natural ventilation may lead to indoor thermal comfort without mechanical cooling. However, in cases where the wind effect is not well captured especially in single side ventilation, then solar–induced ventilation may be a viable alternative. Solar induced ventilation standing involved temperature difference experiments which can be done using both physical modeling and computer simulation (Computational Fluid Dynamics). Solar induced, especially vertical solar chimney ventilation combined air movement and solar radiation simulation. They have different input data which depend on the climatic data of the selected location. This paper evaluates the parametric study strategies in pilot testing, terrace house model and previous research model by simulation and experiment for solar induced ventilation in tropical condition. Comparison of the results of simulations and experiments illustrate a good agreement between numerical and experimental results. These results encourage further research to develop the vertical solar chimney suitable for tropical condition.